Continuous real-time detection and management of comprehensive mental states using wireless soft multifunctional bioelectronics - Kim, Hodam; Kim, Hojoong; Lee, Yoon Jae; Yi, Hoon; Kwon, Youngjin; Huang, Yunuo; Trotti, Lynn Marie; Kim, Yun Soung; Yeo, Woon-Hong (Biosensors & bioelectronics, 2025)
Quantitatively measuring human mental states that profoundly affect cognition, behavior, and recovery would revolutionize personalized digital healthcare. Detecting fatigue, stress, and sleep is particularly important due to their interdependence: persistent fatigue can induce cognitive stress, while chronic stress impairs sleep quality, creating a harmful feedback loop. Here, we introduce a wireless, soft, multifunctional bioelectronic system offering the continuous real-time detection and management of comprehensive mental states. The all-in-one wearable device, mounted on the forehead, measures clinical-grade brain and cardiorespiratory signals. This membrane biopatch is imperceptible, flexible, and reusable, providing ultimate user comfort while detecting high-fidelity electroencephalogram, electrooculogram, pulse rate, and blood oxygen saturation. A set of in vivo studies with human subjects demonstrates that the soft device has great skin-conformal contact and minimized motion artifacts, capturing clinical-quality data with different activities, even during sleep. The developed signal processing methods and deep-learning algorithms offer automated, real-time classification of driving drowsiness, stress conditions, and sleep quality. The bioelectronics platforms in this study have the potential to revolutionize digital healthcare, particularly personalized medicine and at-home health monitoring.